QUANTITATIVE ASSAY OF ASPIRIN AND (SALICYLIC ACID AND HEAVY METALS AS IMPURATIES) IN IRAQI’S MARKET ASPIRIN TABLETS USING DIFFERENT ANALYTICAL METHODS - Saeed, Ahmed Mahdi; Hamzah, Mohammed Jassim; Ahmed, Noor Qasim (International Journal of Applied Pharmaceutics, 2018)
Objective: Easy and precise methods were developed for estimation of aspirin (ASP), impurities from such as salicylic acid (SAL) and heavy metal ions (HMI) in ASP tablets that available in the Iraqi’s market using High-performance liquid chromatography (HPLC), UV–VIS spectrophotometry and atomic absorption spectrophotometric (AAS). Methods: HPLC separation was carried out using C18 as stationary phase and acetonitrile (ACN): water in the ratio of (10: 90 v/v) as a mobile phase for HPLC method and as a solvent for UV-VIS spectrophotometric for quantitative ASP and SAL at 254 nm for HPLC, 226 and 296 nm for UV measurements. AAS was used for HMI determination. Results: ASP and SAL gave absorbance maxima at 226 and 296 nm in ACN: H2O solvent. The Beer’s law was obeyed in the range of 0.05-20 for ASP and 0.02-8 µg/ml for SAL. Correlation coefficients (R2) were 0.9996 and 0.9992 for ASP and SAL respectively, for HPLC and LOD value was 0.006 for ASP and 0.004 μg/ml for SAL. The % recovery for the developed method was found to be in the range of (98.80 to 101.26%) and (98.67 to 103.33%) for ASP and SAL respectively, within the acceptable range, that approved by world health organization (WHO). Conclusion: The proposed method can help research studies, quality control and routine analysis with lesser resources available. The results of the assay of pharmaceutical formulation of the developed method are highly reliable and reproducible and is in good agreement with the label claim of the medicines.